Identification of positively selected genes in Mycobacterium tuberculosis from southern Xinjiang Uygur autonomous region of China - Deng, Lele; Wang, Quan; Liu, Haican; Jiang, Yi; Xu, Miao; Xiang, Yu; Yang, Ting; Yang, Shuliu; Yan, Di; Li, Machao; Zhao, Lili; Zhao, Xiuqin; et al. (Frontiers in Microbiology, 2024)
Background: Tuberculosis (TB) mainly caused by Mycobacterium tuberculosis (Mtb), remains a serious public health problem. Increasing evidences support that selective evolution is an important force affecting genomic determinants of Mtb phenotypes. It is necessary to further understand the Mtb selective evolution and identify the positively selected genes that probably drive the phenotype of Mtb.Methods: This study mainly focused on the positive selection of 807 Mtb strains from southern Xinjiang of China using whole genome sequencing (WGS). The PAML software was used for identifying the genes and sites under positive selection in 807 Mtb strains.Results: Lineage 2 (62.70%) strains were the dominant strains in this area, followed by lineage 3 (19.45%) and lineage 4 (17.84%) strains. There were 239 codons in 47 genes under positive selection, and the genes were majorly associated with functions of transcription, defense mechanisms, and cell wall/membrane/envelope biogenesis. There were 28 codons (43 mutations) in eight genes (gyrA, rpoB, rpoC, katG, pncA, embB, gid, and cut1) under positive selection in multi-drug resistance (MDR) strains but not in drug susceptible (DS) strains, in which 27 mutations were drug-resistant loci, nine mutations were non-drug-resistant loci but in drug-resistant genes, two mutations were compensatory mutations, and five mutations were in unknown drug-resistant gene of cut1. There was a codon in